Intra- and inter-individual variations in the daily haemoglobin and hematocrit concentration in elite cross country skiers caused by different body positions, state of hydration, exercise and altitude - Engelmeyer, E.; de Marees, M.; Achtzehn, S.; Lundby, C.; Saltin, B.; Mester, J. (Science and Skiing IV, 2008)
INTRODUCTION: Variations in the haemoglobin concentration (Hb) occur during day and night time, by fluctuations in plasma volume and also under certain conditions, such as different body positions, the amount of water intake, after training and also under hypoxic conditions (Lundby et al 2004; Heinicke et al 2005; Wehrling et al 2006). The Hb concentration is used äs an indicator for adaptation processes concerning the oxygen carrying capacity of the blood and therefore for the endurance capacity of the athletes. This factor is limited to 16/17 g/dl female/male by the FIS to prevent health risks. The aim of the study was to investigate the basic individual variability and the overall effects of different interventions. A live-high train-high (LH-TH) training program was conducted at 1500-1800m (LH) and -3000m (TH), respectively. Changes in Position were sitting vs. lying down), Status of hydration (2l, 0.51 water intake and no water intake).